Digital Innovations and Market Dynamics of Tourism Businesses in Turkey - Özturan, Nadzeya; Ören, Ali Şahin; Çakar , Sevgin Şahin (PT. Sangadji Media Publishing, 2024)
This research explores the intricate relationship between digital innovations and market dynamics within the Turkish tourism businesses. Employing a qualitative approach, data were gathered through in-depth interviews with key stakeholders, including representatives from tourism agencies, hoteliers, tour operators, and technology providers. Thematic analysis of the data revealed several key findings. Firstly, digital innovations have enabled tourism businesses to enhance customer engagement and deliver personalized experiences, leveraging social media, online booking platforms, and mobile applications. Secondly, technology adoption has led to improved operational efficiency and cost reduction through automation and optimization of various processes. Thirdly, digital platforms have facilitated market expansion and global reach, enabling businesses to tap into new markets and attract international tourists. However, challenges such as digital literacy, data privacy concerns, and the need for government support remain prevalent. Collaboration between the public and private sectors is crucial in driving digital transformation and fostering sustainable growth in the Turkish tourism industry. While the qualitative nature of this study limits generalizability, future research endeavors could explore longitudinal trends, conduct comparative studies across regions, and investigate the role of emerging technologies. Overall, this study contributes to a deeper understanding of the impact of digital innovations on the Turkish tourism sector and provides valuable insights for academia, industry practitioners, and policymakers alike.